Social Information Processing in Substance Use Disorders: Insights From an Emotional Go-Nogo Task - Bjork, James M.; Keyser-Marcus, Lori; Vassileva, Jasmin; Ramey, Tatiana; Houghton, David C.; Moeller, F. Gerard (Frontiers in Psychiatry, 2021)
Positive social connections are crucial for recovery from Substance Use Disorder (SUD). Of interest is understanding potential social information processing (SIP) mediators of this effect. To explore whether persons with different SUD show idiosyncratic biases toward social signals, we administered an emotional go-nogo task (EGNG) to 31 individuals with Cocaine Use Disorder (CoUD), 31 with Cannabis Use Disorder (CaUD), 79 with Opioid Use Disorder (OUD), and 58 controls. Participants were instructed to respond to emotional faces (Fear/Happy) but withhold responses to expressionless faces in two task blocks, with the reverse instruction in the other two blocks. Emotional faces as non-targets elicited more “false alarm” (FA) commission errors as a main effect. Groups did not differ in rates of hits (correct responses) to fearful faces as targets, but participants with CaUD and CoUD showed reduced rates of hits (relative to controls) when expressionless faces were targets. OUD participants had worse hit rates (and slower reaction times (RT)) when fearful faces (but not happy faces) were targets. CaUD participants were most affected by instruction effects (respond/’go’ vs withhold response/’no-go’ to emotional face) on discriminability statistic A. Participants were faster to respond to happy face targets than to expressionless faces. However, this pattern was reversed in fearful face blocks in OUD and CoUD participants. This experiment replicated previous findings of the greater salience of expressive face images, and extends this finding to SUD, where persons with CaUD may show even greater bias toward emotional faces. Conversely, OUD participants showed idiosyncratic behavior in response to fearful faces suggestive of increased attentional disruption by fear. These data suggest a mechanism by which positive social signals may contribute to recovery.